Vetālapacīsī : siṃhāsanabatrīśī vārtā 32 mī - Śāmaḷabhaṭa, 18th cent (Śāmaḷabhaṭa, 18th cent. Works. 1960 ;, 1962)
Medieval Gujarati verse verision of Sanskrit stories about Vikramāditya Śakāri, King of Ujjain.